Sulfur hexafluoride (SF6) emission estimates for China: an inventory for 1990-2010 and a projection to 2020 - Fang, X.; Hu, X.; Janssens-Maenhout, G.; J. Wu; Han, J.; Su, S.; J. Zhang; J. Hu (Environ Sci TechnolEnviron Sci Technol, 2013)
Sulfur hexafluoride (SF6) is the most potent greenhouse gas regulated under the Kyoto Protocol, with a high global warming potential. In this study, SF6 emissions from China were inventoried for 1990-2010 and projected to 2020. Results reveal that the highest SF6 emission contribution originates from the electrical equipment sector (about 70%), followed by the magnesium production sector, the semiconductor manufacture sector and the SF6 production sector (each about 10%). Both agreements and discrepancies were found in comparisons of our estimates with previously published data. An accelerated growth rate was found for Chinese SF6 emissions during 1990-2010. Because the relative growth rate of SF6 emissions is estimated to be much higher than those of CO2, CH4, and N2O, SF6 will play an increasing role in greenhouse gas emissions in China. Global contributions from China increased rapidly from 0.9 +/- 0.3% in 1990 to 22.8 +/- 6.3% in 2008, making China one of the crucial contributors to the recent growth in global emissions. Under the examined Business-as-usual (BAU) Scenario, projected emissions will reach 4270 +/- 1020 t in 2020, but a reduction of about 90% of the projected BAU emissions would be obtained under the Alternative Scenario.
Keywords: Air Pollutants/*analysis/history; China; Confidence Intervals; Greenhouse Effect; History, 20th Century; History, 21st Century; Internationality; Sulfur Hexafluoride/*analysis/history; Time Factors